2014
DOI: 10.1016/s1473-3099(13)70338-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pneumococcal Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10) on outpatient antimicrobial purchases: a double-blind, cluster randomised phase 3–4 trial

Abstract: Despite low relative rate reductions the absolute rate reductions were substantial because of the high incidence of the outcome. This reduction would lead to over 12,000 fewer antimicrobial purchases per year in children younger than 24 months in Finland (birth cohort of 60,000 children).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 45 publications
2
62
0
2
Order By: Relevance
“…However, only a small proportion of nonlaboratory-confirmed invasive pneumococcal disease episodes also had the primary discharge diagnosis of pneumonia or acute otitis media. Thus, the effect on the endpoints cannot be solely explained by vaccine effect on clinical pneumonia and upper respiratory infections, especially because the reported vaccine effectiveness estimates against clinical pneumonia 9 and respiratory tract infections 10 were far below those for non-confirmed invasive pneumococcal disease in our study. For the most sensitive endpoint of register-based non-confirmed invasive pneumococcal disease or unspecified sepsis, the vaccine effectiveness estimates were lower than for other endpoints because of the lower specificity of this endpoint (table 2).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, only a small proportion of nonlaboratory-confirmed invasive pneumococcal disease episodes also had the primary discharge diagnosis of pneumonia or acute otitis media. Thus, the effect on the endpoints cannot be solely explained by vaccine effect on clinical pneumonia and upper respiratory infections, especially because the reported vaccine effectiveness estimates against clinical pneumonia 9 and respiratory tract infections 10 were far below those for non-confirmed invasive pneumococcal disease in our study. For the most sensitive endpoint of register-based non-confirmed invasive pneumococcal disease or unspecified sepsis, the vaccine effectiveness estimates were lower than for other endpoints because of the lower specificity of this endpoint (table 2).…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, we have reported comparable vaccine effectiveness estimates for the infant three plus one and two plus one schedules for all other study outcomes of culture-confirmed invasive pneumococcal disease, 4 pneumonia, 9 and antimicrobial purchases. 10 We are aware of only two published studies 11,12 by Simonsen and colleagues in which the same kind of discharge register-based endpoint was used (panel 2). In these observational studies, the investigators used register-based invasive pneumococcal disease treatment in hospital from a hospital discharge register as the endpoint, but they did not have data for whether these cases were cultureconfirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the rate of antibiotic-resistant invasive pneumococcal infections has decreased in young children and older adults with the widespread use of pneumococcal conjugate vaccines (41). Palmu et al (42) performed an innovative cluster randomized controlled trial using data from a national registry of antibiotic purchases to show that vaccination of every 5 children with the 10-valent pneumococcal H. influenzae protein D conjugate vaccine prevented one antibiotic purchase. A growing body of evidence supports the concept that vaccines to prevent otitis media and exacerbations of COPD will have a broad impact in reducing antimicrobial use, an important contributor to the global burden of antimicrobial resistance (43,44).…”
Section: Vaccines To Reduce Antimicrobial Resistancementioning
confidence: 99%
“…Ultimately, vaccines can extend the clinical utility of antibiotics by reducing infections and limiting their transmission, this impact in turn allows antimicrobials to be used more sparingly and under closer supervision. For example, a Finnish study found that the introduction of a pneumococcal vaccine covering more strains reduced antibiotic purchases by 8% [68].…”
Section: Role Of Vaccines In the Global Fight Against Amrmentioning
confidence: 99%